2012
DOI: 10.1002/bjs.8750
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of glutamine-supplementedversusstandard parenteral nutrition in infants with surgical gastrointestinal disease

Abstract: ISRCTN83168963 (http://www.controlled-trials.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Strong consensus [81,[141][142][143][144][145][146][147][148] In critically ill children, does continuous feeding compared to intermittent bolus gastric feeding impact on outcomes?…”
Section: Discussionmentioning
confidence: 99%
“…Strong consensus [81,[141][142][143][144][145][146][147][148] In critically ill children, does continuous feeding compared to intermittent bolus gastric feeding impact on outcomes?…”
Section: Discussionmentioning
confidence: 99%
“…Even if glutamine supplementation during PN did not reduce the incidence of sepsis in Group 2 of infants with surgical gastrointestinal disease, 74 , 75 it is still debated whether its role in the maintenance and repair of gastrointestinal mucosa may prevent PNAC/IFALD by protecting the hepatic function. A pilot RCT 75 with inadequate sample size (LoE 2b) on Group 2 of infants with surgical gastrointestinal disease showed that enteral glutamine supplementation had no apparent effect on the duration of PN, tolerance of enteral feeds, or intestinal absorptive or barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind, randomized trial, short-term glutamine-supplementation (0.4 g/kg/day) of PN did not show any benefit on intestinal permeability in newborns and infants after major digestive-tract surgery [79]. Similarly, in a recent randomized clinical trial of glutamine-supplemented versus standard PN, glutamine supplementation did not reduce the incidence of sepsis in surgical infants with gastrointestinal disease [85]. Thus, using the Cochrane Central Register of Controlled Trials (The Cochrane Library, 2011, Issue 4), MEDLINE, EMBASE and CINAHL (to November 2011), conference proceedings and previous reviews, it has been recently concluded that the available trial data do not provide evidence that glutamine supplementation confers important benefits for preterm infants [102].…”
Section: Randomized Experimental and Clinical Studies Of Glutaminementioning
confidence: 99%